Russian renewable energy the potential for international cooperation - Øverland, Indra (Routledge is an imprint of the Taylor & Francis Group, an informa business, 2009)
This book provides a balanced analysis of Russia's impressive, understudied and sometimes surprising strengths in the renewable energy sector. The work is a first of its kind, exploring the significant political and economic obstacles to developing renewable energy in Russia. The volume explores whether effective partnerships may be achieved by combining Russia's excellence in basic research and its diverse natural resources with Western management skills - and aiming for innovation and exports